A multi-layer high-frequency PCB board and its preparation method
By adopting a multi-layer structure of composite film material and composite aerogel material in the PCB board, combined with thermal pressing technology, the problems of poor heat dissipation effect and high-frequency performance of PCB boards in the prior art are solved, and higher performance and lower consumption are achieved.
Patent Information
- Application Number
- CN202411807481.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, the heat dissipation effect and high-frequency performance of PCB boards are poor, making it difficult to meet the needs of modern electronic products for high integration, high performance and low consumption.
A multi-layer structure consisting of composite film material and composite aerogel material is adopted to fix each layer through thermal pressing technology to improve the high-frequency performance and heat dissipation efficiency of PCB boards. The composite film material is made of materials such as 2,6-dichlorobenzonitrile, bisphenol AF, pentafluorostyrene and polyurethane prepolymers. The composite aerogel material is composed of nanopolymerized fibers and silicon-containing polymers.
It significantly improves the high-frequency performance and heat dissipation performance of multi-layer PCB boards, extends service life, and meets the needs of modern electronic products for high performance and low consumption.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PCB board preparation, and in particular relates to a multi-layer high-frequency PCB board and a preparation method thereof. Background Art
[0002] With the continuous advancement of integrated circuit technology, the number of components on a single chip has increased dramatically, which has put forward higher requirements for the line density and performance of PCB. Traditional single-sided or double-sided boards can no longer meet the needs of modern electronic products for high integration, high performance and low consumption. Therefore, multi-layer circuit board technology came into being.
[0003] Multilayer PCB refers to a printed circuit board with multiple independent circuit layers formed by stacking metal conductive layers multiple times on a substrate. This design not only significantly improves the line density, but also allows for more complex circuit functions, thereby greatly improving the performance and reliability of electronic products. Especially in high-frequency applications, such as 5G communication equipment, smart phones, tablets, and IoT devices, the role of multilayer PCB boards is more prominent. These devices require fast data transmission speed, large capacity, low latency, and smaller and smaller product size with more and more functions. Multilayer PCB boards are the ideal solution to meet these needs.
[0004] Patent CN104378932A discloses a method for manufacturing a multi-layer PCB board and a multi-layer PCB board. The method includes: stacking N double-layer substrates, M dummy double-layer substrates and at least N+M-1 semi-cured PP sheets to form a structure to be pressed, and the adjacent double-layer substrates and the double-layer substrates and the dummy double-layer substrates are separated by the PP sheets respectively, wherein N and M are natural numbers, and N≥1, M≥1; pressing the structure to be pressed; wherein the structure to be pressed is symmetrical about the middle section; the metal layer on the surface of one side of the dummy double-layer substrate is missing. The multi-layer PCB board prepared by the invention reduces the warping of the multi-layer PCB board formed after pressing and improves the molding quality, but the high frequency and heat dissipation performance of the PCB board prepared by this method still have room for improvement. Summary of the invention
[0005] The object of the present invention is to provide a multi-layer high-frequency PCB board and a preparation method thereof, so as to solve the technical problems of poor heat dissipation effect and high-frequency performance of the PCB board in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a multi-layer high-frequency PCB board, which consists of an inner layer board, a heat dissipation layer and an outer layer board, and the inner layer board, the heat dissipation layer and the outer layer board are arranged in sequence from the inside to the outside, the surface of the inner layer board is covered with a composite film, the heat dissipation layer is composed of a composite aerogel material, and the layers are fixed by a hot pressing technology.
[0008] Preferably, the method for preparing the composite membrane material comprises the following steps:
[0009] Q1: 2,6-dichlorobenzonitrile, bisphenol AF, potassium carbonate, N-methylpyrrolidone and toluene are added to a container, and the temperature is raised to react. After the reaction is completed, the temperature is further raised to react. After the reaction is completed, the temperature is lowered, and pentafluorostyrene, potassium carbonate and N-methylpyrrolidone are added to react. After the reaction is completed, the reactants are added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified, and dried to obtain product 1;
[0010] Q2: Add the polyurethane prepolymer into deionized water, stir rapidly, then add product 1, continue stirring, heat and cure to obtain a composite membrane material.
[0011] In the above process, 2,6-dichlorobenzonitrile and bisphenol AF undergo a nucleophilic substitution reaction, and the chlorine atom in 2,6-dichlorobenzonitrile is replaced by the phenolic hydroxyl group in bisphenol AF to form a cross-linked structure. Subsequently, pentafluorostyrene is grafted to the end of the polymer chain through a free radical polymerization reaction to obtain product 1. The foaming process of the polyurethane prepolymer causes the composite film material to be filled with foam and has a low dielectric constant. The synthetic reaction formula of product 1 is as follows:
[0012]
[0013] Preferably, in Q1, the molar ratio of 2,6-dichlorobenzonitrile, bisphenol AF, toluene and pentafluorostyrene is (0.15-0.3): (0.15-0.25): (0.03-0.045): (0.016-0.033), the heating reaction temperature is 140-150°C, the time is 2-3h, the heating reaction temperature is continued to be 180-185°C, the time is 1-2h, the cooling temperature is 120-125°C, the time is 5-7h, and the purification is carried out with boiling water and anhydrous ethanol, and the drying temperature is 100-110°C, and the time is 20-24h.
[0014] Preferably, in Q2, the usage ratio of the polyurethane prepolymer, deionized water and product 1 is (3-8) g: (10-15) mL: (18-23) g, the rapid stirring time is 10-15 s, the continued stirring time is 20-30 s, the heating curing temperature is 50-55° C., and the time is 20-24 h.
[0015] Preferably, the method for preparing the composite aerogel material comprises the following steps:
[0016] S1: Add N,N-dimethylacetamide to a container, add 2-(4-aminophenyl)-5-aminobenzimidazole and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl in sequence under stirring, stir until completely dissolved, then continue to add pyromellitic anhydride, 4,4'-biphenyl ether dianhydride and N,N-dimethylacetamide, react at low temperature to obtain a polymerization solution, and obtain nano-polymer fibers by electrospinning;
[0017] S2: 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane are added to a container, and after mixing by magnetic stirring, trifluoromethanesulfonic acid is added, and the mixture is heated under a nitrogen atmosphere for reaction. After the reaction, an excess of hexamethyldisilazane is added, and magnetic stirring is performed. After the stirring is completed, water is removed, stirring is continued, filtering is performed, impurities are removed, and reduced pressure distillation is performed to obtain a silicon-containing polymer;
[0018] S3: adding the obtained nano polymer fiber to the tert-butyl alcohol solution, dispersing it to obtain a dispersion, adding the silicon-containing polymer to the dispersion, stirring it at high speed to obtain a mixed dispersion, freeze-drying it, and heat-treating it to obtain a composite aerogel material.
[0019] In the above process, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, pyromellitic anhydride and 4,4'-biphenyl ether dianhydride are first used as raw materials to prepare nano polymer fibers with a cross-linked structure through reaction, and then 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane are used as raw materials to prepare silicon-containing polymers, and the silicon-containing polymers are uniformly distributed in the nano polymer fibers through a sol blending method to form a composite aerogel material with a double network structure, wherein the synthesis reaction formula of the silicon-containing polymer is as follows:
[0020]
[0021] Preferably, in S1, the amount ratio of N,N-dimethylacetamide, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, pyromellitic anhydride, 4,4'-biphenyl ether dianhydride added first and N,N-dimethylacetamide added last is (40-50) mL: (2.2-2.64) g: (3.1-3.72) g: (3.43-4.12) g: (1.2 2-1.46)g: (20-25)mL, stir for 10-20min until completely dissolved, low temperature reaction temperature is 0-2℃, reaction time is 10-12h, during electrospinning: spinning temperature is 28-32℃, ambient humidity is 50-60%, polymerization solution advancement speed is 0.008-0.01mm / min, voltage is 20-25kV, roller speed is 400-420rpm, distance from needle to receiving plate is 18-20cm.
[0022] Preferably, in S2, the dosage ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, 1,1,3,3-tetramethyldisiloxane and trifluoromethanesulfonic acid is (2.5-5) g: (18.7-36) g: (0.27-0.5) g: (4-7) μL, the magnetic stirring time is 20-30 min, the heating stirring temperature is 50-60°C, the time is 48-52 h, the magnetic stirring time is 2-4 h, water is removed with anhydrous sodium sulfate, and stirring is continued for 5-8 h.
[0023] Preferably, in S3, the amount ratio of the nano-polymer fiber, the tert-butyl alcohol solution and the silicon-containing polymer is (1-1.5) g: (75-125) g: (25-40) g, and a high-speed homogenizer is used for 30 minutes of dispersion treatment under a high pressure of 1000 bar, the high-speed stirring time is 10-15 minutes, the freeze-drying time is 70-74 hours, and the heat treatment temperature is 300-320°C.
[0024] Preferably, the method for preparing a multi-layer high-frequency PCB board comprises the following steps:
[0025] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven to heat and cure to obtain an inner layer board with a composite film on the surface;
[0026] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0027] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0028] Preferably, in step one, the temperature rising and curing process is: 80°C / 1h, 100°C / 1h, 120°C / 1h, 140°C / 1h, 160°C / 2h, 200°C / 4h.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] 1. The present invention first uses 2,6-dichlorobenzonitrile, bisphenol AF, pentafluorostyrene and polyurethane prepolymer as raw materials to prepare a composite film material, which is coated on the surface of the inner layer board to effectively improve the high-frequency performance of the multi-layer PCB board. Subsequently, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, pyromellitic anhydride, 4,4'-biphenyl ether dianhydride, 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane are used as raw materials to prepare a composite aerogel material, which is used as a part of the multi-layer PCB board to effectively improve its heat dissipation performance and extend the service life of the multi-layer PCB board.
[0031] 2. The prepared composite film material is evenly covered on the surface of the inner layer, which can effectively improve the high-frequency performance of the multi-layer PCB. The tetrafluorostyrene group is introduced into the composite film material. The fluorine atom has a large electronegativity and a small atomic radius, which can form a dense stacking in the molecular chain, making the electron cloud density distribution more uniform, thereby reducing the polarization ability of the molecule. The presence of the cross-linked structure enhances the interaction between the molecular chains, reduces the free movement of the molecular chains, and reduces the dielectric constant. At the same time, the foam formed by the foaming of the polyurethane prepolymer is used as a filler to form a porous structure in the composite film material. The presence of pores can accommodate and disperse the charge in the electric field, reduce the accumulation and polarization of the charge in the material, reduce the dielectric constant, and thus increase the high-frequency performance of the PCB.
[0032] 3. The prepared composite aerogel material is used as the heat dissipation layer of the PCB board, which can effectively improve the heat dissipation efficiency of the PCB board. The double network structure contained in the composite aerogel material is composed of nano-polymer fibers and silicon-containing polymers. The nano-polymer fibers serve as the main heat conduction channel, and together with the silicon-containing polymers filled between the fibers, they form a complex heat dissipation path, so that heat can be quickly transferred and dispersed inside the material. In addition, the nano-effect of the nano-polymer fibers increases the specific surface area and pore structure of the material. The existence of the pore structure is like a "reservoir" of heat, which effectively buffers and disperses heat. At the same time, the nano-scale fibers diversify the heat conduction path, further improving the heat dissipation performance. The silicon-containing polymer can maintain the integrity of the structure at high temperatures due to its excellent thermal stability and chemical stability, thereby ensuring the heat dissipation performance of the material in a high temperature environment. DETAILED DESCRIPTION
[0033] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Embodiment 1: This embodiment discloses a method for preparing a composite film material, comprising the following steps:
[0035] Q1: 1.55 g 2,6-dichlorobenzonitrile, 2.69 g bisphenol AF, 0.99 g potassium carbonate, 4 mL N-methylpyrrolidone and 0.16 mL toluene were added to a container, heated to 150°C for reaction for 3 h, and then heated to 185°C for reaction for 1 h. After the reaction, the temperature was lowered to 125°C, and 0.19 g pentafluorostyrene, 0.17 g potassium carbonate and 38.8 mL N-methylpyrrolidone were added and reacted for 5 h. After the reaction, the reactants were added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified with boiling water and anhydrous ethanol, and dried at 100°C for 24 h to obtain product 1;
[0036] Q2: Add 5.5 g of polyurethane prepolymer to 12.5 mL of deionized water, stir rapidly for 10 seconds, add 20.5 g of product 1, continue stirring for 25 seconds, heat and cure at 50°C for 24 hours to obtain a composite membrane material.
[0037] This embodiment discloses a method for preparing a composite aerogel material, comprising the following steps:
[0038] S1: 45 mL of N, N-dimethylacetamide was added to a container, and 2.42 g of 2-(4-aminophenyl)-5-aminobenzimidazole and 3.41 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl were added in sequence under stirring. After stirring for 15 min until the mixture was completely dissolved, 3.72 g of pyromellitic anhydride, 1.34 g of 4,4'-biphenyl ether dianhydride and 22.5 mL of N, N-dimethylacetamide were added, and the mixture was reacted at 2°C for 12 h to obtain a polymerization solution. The polymerization solution was electrospun at a spinning temperature of 30°C, an ambient humidity of 55%, a polymerization solution propulsion speed of 0.008 mm / min, a voltage of 22.5 kV, a roller speed of 420 rpm, and a distance from the needle to the receiving plate of 20 cm to obtain nano-polymer fibers.
[0039] S2: 3.75 g of 1,3,5,7-tetramethylcyclotetrasiloxane, 27.3 g of trifluoropropylmethylcyclotrisiloxane and 0.38 g of 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred for 30 min, 5.5 μL of trifluoromethanesulfonic acid was added, and the mixture was heated at 60° C. for 48 h under a nitrogen atmosphere. After the reaction, excess hexamethyldisilazane was added and magnetically stirred for 4 h. After the stirring was completed, water was removed with anhydrous sodium sulfate, stirring was continued for 6 h, filtration was performed, impurities were removed, and reduced pressure distillation was performed to obtain a silicon-containing polymer;
[0040] S3: Add 1.25 g of the obtained nano-polymer fibers to 100 g of tert-butanol solution, use a high-speed homogenizer to perform dispersion treatment at a high pressure of 1000 bar for 30 minutes to obtain a dispersion liquid, add 32.5 g of the silicon-containing polymer to the dispersion liquid, stir at a high speed for 15 minutes to obtain a mixed dispersion liquid, freeze-dry for 72 hours, and heat-treat at 320°C to obtain a composite aerogel material.
[0041] This embodiment discloses a method for preparing a multi-layer high-frequency PCB board, comprising the following steps:
[0042] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven for heating and curing. The heating and curing process is: 80℃ / 1h, 100℃ / 1h, 120℃ / 1h, 140℃ / 1h, 160℃ / 2h, 200℃ / 4h, and obtain an inner layer board with a composite film on the surface;
[0043] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0044] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0045] Embodiment 2: This embodiment discloses a method for preparing a composite film material, comprising the following steps:
[0046] Q1: 1.032 g 2,6-dichlorobenzonitrile, 2.02 g bisphenol AF, 0.99 g potassium carbonate, 4 mL N-methylpyrrolidone and 0.13 mL toluene were added to a container, heated to 150°C for reaction for 3 h, and then heated to 185°C for reaction for 1 h. After the reaction, the temperature was lowered to 125°C, and 0.124 g pentafluorostyrene, 0.17 g potassium carbonate and 38.8 mL N-methylpyrrolidone were added and reacted for 5 h. After the reaction, the reactants were added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified with boiling water and anhydrous ethanol, and dried at 100°C for 24 h to obtain product 1;
[0047] Q2: Add 3 g of polyurethane prepolymer into 10 mL of deionized water, stir rapidly for 10 seconds, then add 18 g of product 1, continue stirring for 25 seconds, heat and cure at 50°C for 24 hours to obtain a composite membrane material.
[0048] This embodiment discloses a method for preparing a composite aerogel material, comprising the following steps:
[0049] S1: 40 mL of N, N-dimethylacetamide was added to a container, and 2.2 g of 2-(4-aminophenyl)-5-aminobenzimidazole and 3.1 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl were added in sequence under stirring. After stirring for 15 min until the mixture was completely dissolved, 3.43 g of pyromellitic anhydride, 1.22 g of 4,4'-biphenyl ether dianhydride and 20 mL of N, N-dimethylacetamide were added, and the mixture was reacted at 2°C for 12 h to obtain a polymerization solution. The polymerization solution was electrospun at a spinning temperature of 30°C, an ambient humidity of 55%, a polymerization solution propulsion speed of 0.008 mm / min, a voltage of 22.5 kV, a roller speed of 420 rpm, and a distance from the needle to the receiving plate of 20 cm to obtain nano-polymer fibers.
[0050] S2: 2.5 g of 1,3,5,7-tetramethylcyclotetrasiloxane, 18.7 g of trifluoropropylmethylcyclotrisiloxane and 0.27 g of 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred for 30 min, 4 μL of trifluoromethanesulfonic acid was added, and the mixture was heated at 60° C. for 48 h under a nitrogen atmosphere. After the reaction, excess hexamethyldisilazane was added and magnetically stirred for 4 h. After the stirring was completed, water was removed with anhydrous sodium sulfate, stirring was continued for 6 h, filtration was performed, impurities were removed, and reduced pressure distillation was performed to obtain a silicon-containing polymer;
[0051] S3: Add 1.5 g of the obtained nano-polymer fibers to 125 g of tert-butanol solution, use a high-speed homogenizer to perform dispersion treatment at a high pressure of 1000 bar for 30 minutes to obtain a dispersion liquid, add 25 g of the silicon-containing polymer to the dispersion liquid, stir at a high speed for 15 minutes to obtain a mixed dispersion liquid, freeze-dry for 72 hours, and heat-treat at 320°C to obtain a composite aerogel material.
[0052] This embodiment discloses a method for preparing a multi-layer high-frequency PCB board, comprising the following steps:
[0053] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven for heating and curing. The heating and curing process is: 80℃ / 1h, 100℃ / 1h, 120℃ / 1h, 140℃ / 1h, 160℃ / 2h, 200℃ / 4h, and obtain an inner layer board with a composite film on the surface;
[0054] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0055] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0056] Embodiment 3: This embodiment discloses a method for preparing a composite film material, comprising the following steps:
[0057] Q1: 2.064 g 2,6-dichlorobenzonitrile, 3.36 g bisphenol AF, 0.99 g potassium carbonate, 4 mL N-methylpyrrolidone and 0.19 mL toluene were added to a container, heated to 150°C for reaction for 3 h, and then heated to 185°C for reaction for 1 h. After the reaction, the temperature was lowered to 125°C, and 0.256 g pentafluorostyrene, 0.17 g potassium carbonate and 38.8 mL N-methylpyrrolidone were added and reacted for 5 h. After the reaction, the reactants were added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified with boiling water and anhydrous ethanol, and dried at 100°C for 24 h to obtain product 1;
[0058] Q2: 8 g of polyurethane prepolymer was added to 15 mL of deionized water, and after rapid stirring for 10 seconds, 23 g of product 1 was added, and stirring was continued for 25 seconds. The mixture was heated and cured at 50°C for 24 hours to obtain a composite membrane material.
[0059] This embodiment discloses a method for preparing a composite aerogel material, comprising the following steps:
[0060] S1: 50 mL of N, N-dimethylacetamide was added to a container, and 2.64 g of 2-(4-aminophenyl)-5-aminobenzimidazole and 3.72 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl were added in sequence under stirring. After stirring for 15 min until the mixture was completely dissolved, 4.12 g of pyromellitic anhydride, 1.46 g of 4,4'-biphenyl ether dianhydride and 25 mL of N, N-dimethylacetamide were added, and the mixture was reacted at 2°C for 12 h to obtain a polymerization solution. The polymerization solution was electrospun at a spinning temperature of 30°C, an ambient humidity of 55%, a polymerization solution propulsion speed of 0.008 mm / min, a voltage of 22.5 kV, a roller speed of 420 rpm, and a distance from the needle to the receiving plate of 20 cm to obtain nano-polymer fibers.
[0061] S2: 5 g of 1,3,5,7-tetramethylcyclotetrasiloxane, 36 g of trifluoropropylmethylcyclotrisiloxane and 0.5 g of 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred for 30 min, 7 μL of trifluoromethanesulfonic acid was added, and the mixture was heated at 60° C. for 48 h under a nitrogen atmosphere. After the reaction, excess hexamethyldisilazane was added and magnetically stirred for 4 h. After the stirring was completed, water was removed with anhydrous sodium sulfate, stirring was continued for 6 h, filtration was performed, impurities were removed, and reduced pressure distillation was performed to obtain a silicon-containing polymer;
[0062] S3: Add 1 g of the obtained nano-polymer fiber to 75 g of tert-butanol solution, use a high-speed homogenizer to perform dispersion treatment at a high pressure of 1000 bar for 30 minutes to obtain a dispersion liquid, add 40 g of the silicon-containing polymer to the dispersion liquid, stir at a high speed for 15 minutes to obtain a mixed dispersion liquid, freeze-dry for 72 hours, and heat-treat at 320°C to obtain a composite aerogel material.
[0063] This embodiment discloses a method for preparing a multi-layer high-frequency PCB board, comprising the following steps:
[0064] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven for heating and curing. The heating and curing process is: 80℃ / 1h, 100℃ / 1h, 120℃ / 1h, 140℃ / 1h, 160℃ / 2h, 200℃ / 4h, and obtain an inner layer board with a composite film on the surface;
[0065] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0066] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0067] Embodiment 4: This embodiment discloses a method for preparing a composite film material, comprising the following steps:
[0068] Q1: 1.291 g 2,6-dichlorobenzonitrile, 2.35 g bisphenol AF, 0.99 g potassium carbonate, 4 mL N-methylpyrrolidone and 0.15 mL toluene were added to a container, heated to 150°C for reaction for 3 h, and then heated to 185°C for reaction for 1 h. After the reaction, the temperature was lowered to 125°C, and 0.157 g pentafluorostyrene, 0.17 g potassium carbonate and 38.8 mL N-methylpyrrolidone were added and reacted for 5 h. After the reaction, the reactants were added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified with boiling water and anhydrous ethanol, and dried at 100°C for 24 h to obtain product 1;
[0069] Q2: Add 4 g of polyurethane prepolymer into 11 mL of deionized water, stir rapidly for 10 seconds, add 19 g of product 1, continue stirring for 25 seconds, heat and cure at 50°C for 24 hours to obtain a composite membrane material.
[0070] This embodiment discloses a method for preparing a composite aerogel material, comprising the following steps:
[0071] S1: 42 mL of N, N-dimethylacetamide was added to a container, and 2.3 g of 2-(4-aminophenyl)-5-aminobenzimidazole and 3.23 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl were added in sequence under stirring. After stirring for 15 min until the mixture was completely dissolved, 3.61 g of pyromellitic anhydride, 1.28 g of 4,4'-biphenyl ether dianhydride and 21 mL of N, N-dimethylacetamide were added, and the mixture was reacted at 2°C for 12 h to obtain a polymerization solution. The polymerization solution was electrospun at a spinning temperature of 30°C, an ambient humidity of 55%, a polymerization solution propulsion speed of 0.008 mm / min, a voltage of 22.5 kV, a roller speed of 420 rpm, and a distance from the needle to the receiving plate of 20 cm to obtain nano-polymer fibers.
[0072] S2: 3.1 g of 1,3,5,7-tetramethylcyclotetrasiloxane, 20 g of trifluoropropylmethylcyclotrisiloxane and 0.31 g of 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred for 30 min, 5 μL of trifluoromethanesulfonic acid was added, and the mixture was heated at 60° C. for 48 h under a nitrogen atmosphere. After the reaction, excess hexamethyldisilazane was added and magnetically stirred for 4 h. After the stirring was completed, water was removed with anhydrous sodium sulfate, stirring was continued for 6 h, filtration was performed, impurities were removed, and reduced pressure distillation was performed to obtain a silicon-containing polymer;
[0073] S3: Add 1.1 g of the obtained nano-polymer fibers to 80 g of tert-butanol solution, use a high-speed homogenizer to perform dispersion treatment at a high pressure of 1000 bar for 30 minutes to obtain a dispersion liquid, add 30 g of a silicon-containing polymer to the dispersion liquid, stir at a high speed for 15 minutes to obtain a mixed dispersion liquid, freeze-dry for 72 hours, and heat-treat at 320°C to obtain a composite aerogel material.
[0074] This embodiment discloses a method for preparing a multi-layer high-frequency PCB board, comprising the following steps:
[0075] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven for heating and curing. The heating and curing process is: 80℃ / 1h, 100℃ / 1h, 120℃ / 1h, 140℃ / 1h, 160℃ / 2h, 200℃ / 4h, and obtain an inner layer board with a composite film on the surface;
[0076] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0077] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0078] Embodiment 5: This embodiment discloses a method for preparing a composite film material, comprising the following steps:
[0079] Q1: 1.807 g 2,6-dichlorobenzonitrile, 2.91 g bisphenol AF, 0.99 g potassium carbonate, 4 mL N-methylpyrrolidone and 0.18 mL toluene were added to a container, heated to 150°C for reaction for 3 h, and then heated to 185°C for reaction for 1 h. After the reaction, the temperature was lowered to 125°C, and 0.231 g pentafluorostyrene, 0.17 g potassium carbonate and 38.8 mL N-methylpyrrolidone were added and reacted for 5 h. After the reaction, the reactants were added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified with boiling water and anhydrous ethanol, and dried at 100°C for 24 h to obtain product 1;
[0080] Q2: 7 g of polyurethane prepolymer was added to 14 mL of deionized water. After rapid stirring for 10 seconds, 22 g of product 1 was added, stirring was continued for 25 seconds, and heating and curing was performed at 50°C for 24 hours to obtain a composite membrane material.
[0081] This embodiment discloses a method for preparing a composite aerogel material, comprising the following steps:
[0082] S1: 48 mL of N, N-dimethylacetamide was added to a container, and 2.51 g of 2-(4-aminophenyl)-5-aminobenzimidazole and 3.65 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl were added in sequence under stirring. After stirring for 15 min until the mixture was completely dissolved, 4.05 g of pyromellitic anhydride, 1.37 g of 4,4'-biphenyl ether dianhydride and 24 mL of N, N-dimethylacetamide were added, and the mixture was reacted at 2°C for 12 h to obtain a polymerization solution. The polymerization solution was electrospun at a spinning temperature of 30°C, an ambient humidity of 55%, a polymerization solution propulsion speed of 0.008 mm / min, a voltage of 22.5 kV, a roller speed of 420 rpm, and a distance from the needle to the receiving plate of 20 cm to obtain nano-polymer fibers.
[0083] S2: 4.5 g of 1,3,5,7-tetramethylcyclotetrasiloxane, 32 g of trifluoropropylmethylcyclotrisiloxane and 0.45 g of 1,1,3,3-tetramethyldisiloxane were added to a container, magnetically stirred for 30 min, 6 μL of trifluoromethanesulfonic acid was added, and the mixture was heated at 60° C. for 48 h under a nitrogen atmosphere. After the reaction, excess hexamethyldisilazane was added and magnetically stirred for 4 h. After the stirring was completed, water was removed with anhydrous sodium sulfate, stirring was continued for 6 h, filtration was performed, impurities were removed, and reduced pressure distillation was performed to obtain a silicon-containing polymer;
[0084] S3: Add 1.4 g of the obtained nano-polymer fibers to 110 g of tert-butanol solution, use a high-speed homogenizer to perform dispersion treatment at a high pressure of 1000 bar for 30 minutes to obtain a dispersion liquid, add 28 g of the silicon-containing polymer to the dispersion liquid, stir at a high speed for 15 minutes to obtain a mixed dispersion liquid, freeze-dry for 72 hours, and heat-treat at 320°C to obtain a composite aerogel material.
[0085] This embodiment discloses a method for preparing a multi-layer high-frequency PCB board, comprising the following steps:
[0086] Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven for heating and curing. The heating and curing process is: 80℃ / 1h, 100℃ / 1h, 120℃ / 1h, 140℃ / 1h, 160℃ / 2h, 200℃ / 4h, and obtain an inner layer board with a composite film on the surface;
[0087] Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board;
[0088] Step 3: Combine the inner layer board with composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board.
[0089] Comparative Example 1: Compared with Example 1, in Comparative Example 1, during the preparation of the composite membrane material, no polyurethane prepolymer is added, and other conditions remain unchanged.
[0090] Comparative Example 2: Compared with Example 1, in Comparative Example 2, during the preparation of the composite aerogel material, no trifluoropropylmethylcyclotrisiloxane was added, and other conditions remained unchanged.
[0091] Comparative Example 3: Compared with Example 1, in Comparative Example 3, during the preparation process of the multi-layer high-frequency PCB board, no composite film material is added, and other conditions remain unchanged.
[0092] Comparative Example 4: Comparative Example 4
[0093] Compared with Example 1, in Comparative Example 4, during the preparation of the multi-layer high-frequency PCB board, FR-4 epoxy resin was used instead of the composite aerogel material, and other conditions remained unchanged.
[0094] Experimental example: The dielectric constant of the sample was measured using the parallel plate method, and the thermal conductivity of the sample was determined according to ASTM E1530. The test results are shown in Table 1:
[0095] project Relative dielectric constant Thermal conductivity / W / (m·K) Example 1 4.01 0.48 Example 2 4.03 0.47 Example 3 4.05 0.45 Example 4 4.03 0.46 Example 5 4.02 0.45 Comparative Example 1 4.37 0.45 Comparative Example 2 4.05 0.32 Comparative Example 3 4.39 0.45 Comparative Example 4 4.08 0.31 Table 1
[0096] The relative dielectric constant has a significant impact on the high frequency of the PCB board. The relative dielectric constant determines the transmission speed of the electrical signal on the PCB board. The lower the relative dielectric constant, the faster the signal transmission speed, which is crucial for the signal transmission speed and receiving sensitivity in high-frequency applications; the higher the thermal conductivity, the better the heat dissipation performance. It can be seen from the test results in Table 1 that the multilayer high-frequency PCB boards prepared by Examples 1-5 of the present invention have excellent high-frequency performance and heat dissipation performance. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of polyurethane prepolymer can make the PCB board have excellent high-frequency performance; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of trifluoropropylmethylcyclotrisiloxane can make the PCB board have excellent heat dissipation performance; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the addition of composite film materials can make the PCB board have excellent high-frequency performance; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the use of composite aerogel materials can make the PCB board have excellent heat dissipation performance.
[0097] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0098] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a multi-layer high-frequency PCB board, characterized in that: The following steps are involved: Step 1: Press the copper foil into an inner layer board, add the composite film material into N-methylpyrrolidone, stir, pour it onto the surface of the inner layer board, and then place it in an oven to heat and cure to obtain an inner layer board with a composite film on the surface; Step 2: Cover the surface of the copper foil with an insulating layer and a protective layer, drill holes, and copper plate to obtain an outer layer board; Step 3: Combine the inner layer board with the composite film on the surface, the composite aerogel material and the outer layer board together through hot pressing technology, and then etch, weld, test and package to obtain a multi-layer high-frequency PCB board; Wherein, the preparation method of the composite membrane material comprises the following steps: Q1: 2,6-dichlorobenzonitrile, bisphenol AF, potassium carbonate, N-methylpyrrolidone and toluene are added to a container, and the temperature is raised to react. After the reaction is completed, the temperature is further raised to react. After the reaction is completed, the temperature is lowered, and pentafluorostyrene, potassium carbonate and N-methylpyrrolidone are added to react. After the reaction is completed, the reactants are added to deionized water containing hydrochloric acid and anhydrous ethanol, crushed by a pulverizer, purified, and dried to obtain product 1; Q2: Add the polyurethane prepolymer to deionized water, stir quickly, add product 1, continue stirring, heat and cure to obtain a composite membrane material; The preparation method of the composite aerogel material comprises the following steps: S1: Add N,N-dimethylacetamide to a container, add 2-(4-aminophenyl)-5-aminobenzimidazole and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl in sequence under stirring, stir until completely dissolved, then continue to add pyromellitic anhydride, 4,4'-biphenyl ether dianhydride and N,N-dimethylacetamide, react at low temperature to obtain a polymerization solution, and obtain nano-polymer fibers by electrospinning; S2: 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane and 1,1,3,3-tetramethyldisiloxane are added to a container, and after mixing by magnetic stirring, trifluoromethanesulfonic acid is added, and the mixture is heated under a nitrogen atmosphere for reaction. After the reaction, an excess of hexamethyldisilazane is added, and magnetic stirring is performed. After the stirring is completed, water is removed, stirring is continued, filtering is performed, impurities are removed, and reduced pressure distillation is performed to obtain a silicon-containing polymer; S3: adding the obtained nano polymer fiber to the tert-butyl alcohol solution, dispersing it to obtain a dispersion, adding the silicon-containing polymer to the dispersion, stirring it at high speed to obtain a mixed dispersion, freeze-drying it, and heat-treating it to obtain a composite aerogel material.
2. The method for preparing a multi-layer high-frequency PCB board according to claim 1, characterized in that: In the Q1, the molar ratio of 2,6-dichlorobenzonitrile, bisphenol AF, toluene and pentafluorostyrene is (0.15-0.3): (0.15-0.25): (0.03-0.045): (0.016-0.033), the heating reaction temperature is 140-150°C, the time is 2-3h, the heating reaction temperature is continued to be 180-185°C, the time is 1-2h, the cooling temperature is 120-125°C, the time is 5-7h, and the product is purified with boiling water and anhydrous ethanol, and the drying temperature is 100-110°C, and the time is 20-24h.
3. The method for preparing a multi-layer high-frequency PCB according to claim 1, characterized in that: In Q2, the usage ratio of polyurethane prepolymer, deionized water and product 1 is (3-8) g: (10-15) mL: (18-23) g, the rapid stirring time is 10-15 s, the continued stirring time is 20-30 s, the heating curing temperature is 50-55° C., and the time is 20-24 h.
4. The method for preparing a multi-layer high-frequency PCB according to claim 1, characterized in that: In S1, the amount ratio of N,N-dimethylacetamide, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, pyromellitic anhydride, 4,4'-biphenyl ether dianhydride added first and N,N-dimethylacetamide added last is (40-50) mL: (2.2-2.64) g: (3.1-3.72) g: (3.43-4.12) g: (1.22-1 .46)g: (20-25)mL, stir for 10-20min until completely dissolved, the low temperature reaction temperature is 0-2℃, the reaction time is 10-12h, during the electrospinning process: the spinning temperature is 28-32℃, the ambient humidity is 50-60%, the polymerization solution advancement speed is 0.008-0.01mm / min, the voltage is 20-25kV, the roller speed is 400-420rpm, and the distance from the needle to the receiving plate is 18-20cm.
5. The method for preparing a multi-layer high-frequency PCB board according to claim 1, characterized in that: In S2, the dosage ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, 1,1,3,3-tetramethyldisiloxane and trifluoromethanesulfonic acid is (2.5-5) g: (18.7-36) g: (0.27-0.5) g: (4-7) μL, the magnetic stirring time is 20-30 min, the heating stirring temperature is 50-60° C., the time is 48-52 h, the magnetic stirring time is 2-4 h, water is removed with anhydrous sodium sulfate, and stirring is continued for 5-8 h.
6. The method for preparing a multi-layer high-frequency PCB board according to claim 1, characterized in that: In the S3, the amount ratio of the nano-polymer fiber, the tert-butyl alcohol solution and the silicon-containing polymer is (1-1.5) g: (75-125) g: (25-40) g, and a high-speed homogenizer is used to perform a dispersion treatment for 30 minutes under a high pressure of 1000 bar, the high-speed stirring time is 10-15 minutes, the freeze-drying time is 70-74 hours, and the heat treatment temperature is 300-320°C.
7. The method for preparing a multi-layer high-frequency PCB board according to claim 1, characterized in that: In the step 1, the temperature rising and curing process is: 80°C / 1h, 100°C / 1h, 120°C / 1h, 140°C / 1h, 160°C / 2h, 200°C / 4h.
Citation Information
Patent Citations
Manufacturing method of multi-layer PCB and multi-layer PCB
CN104378932A
High-frequency low-loss multilayer FPC and production process thereof
CN112689383A
High-heat-dissipation metal aluminum-based copper-clad plate
CN116901543A
Cited By
High-frequency and high-speed PCB (printed circuit board) and preparation method thereof
CN121793238A